(untitled) - Stoller, Bryan Michael (Hoboken, NJ., 2009)
With all the recent advancements in filmmaking technology, more people than ever are trying their hand at filmmaking. Keeping up with the newest information in this booming field, this updated edition of Filmmaking For Dummies features up-to-the-minute coverage of the latest and greatest hardware, software, accessories, and trends--including high-definition technology and new outlets for films such as YouTube and MySpace. It demystifies the nuts-and-bolts of filmmaking, from developing a project and securing financing to hiring a cast and crew, editing, and getting distribution. This new edition also provides new movie examples and updated contacts and resources. Whether people want to become professional filmmakers or simply shoot quality home movies, this practical guide has all the advice and tips needed to succeed.
Keywords: Hình ảnh chuyển động,Motion pictures; Sản xuất và chỉ đạo,Production and direction